Sampling--The "Mother Lode" of All Errors. - McConnell, John; Nunnally, Brian; McGarvey, Bernard (Journal of Validation Technology (JVT))
Before analytical error can be reduced, it must be understood. This means being able to separate assay and sampling error. A hierarchical study is an effective way to separate assay, sampling, and process errors. A hierarchical study retains the time order sequence of the data, making process investigation and improvement simpler. The best estimates for analytical error are produced by blind controls. A hierarchical study can provide an effective de facto blind control.